Does corporate green ranking reflect carbon-mitigation performance?. (20th December 2020) - Guo, Ting; Zha, Guiliang; Lee, Chyi Lin; Tang, Qingliang
Abstract: To offer a roadmap for companies to achieve best practices, a new green-ranking system has been launched by the CDP, formerly the Carbon Disclosure Project. This new system, which takes its data from firms' disclosure of their own carbon-reduction efforts, classifies companies into four ranks, namely, A (leadership), B (management), C (awareness) and D (disclosure), where a higher ranking indicates a greener company. This system replaced the old carbon-disclosure scoring system. However, as participation in the survey that collects the data is voluntary, there is a concern that the carbon disclosure could be a green-washing activity, used for impression management. It is not clear whether this new system can resolve this issue. This study investigates whether corporate green rankings are more closely associated with carbon reduction than carbon-disclosure scoring. We use innovative methods to detect green-washing behaviour by examining the degree of correlation between carbon disclosure and performance versus between green rank and performance. Our empirical results show that there a significant positive link between green ranking and carbon performance, whereas a positive association between disclosure scoring and carbon performance is not found under the old carbon-reporting mechanism. This likely means that this new system has to a certain extent reduced green washing in our sample firms, among other implications.